The future for treating Creutzfeldt–Jakob disease. (January 2015) - Vetrugno, Vito; Puopolo, Maria; Cardone, Franco; Capozzoli, Fiorentino; Ladogana, Anna; Pocchiari, Maurizio
<x xml:space="preserve">Abstract</x> Introduction: Creutzfeldt–Jakob disease (CJD) is a rare, transmissible and fatal neurodegenerative illness that affects people worldwide with a prevalence of about 1 – 2 cases per million people. Early diagnosis of CJD is still difficult despite recent development of novel assays for detecting the pathological prion protein, the only reliable marker of disease found in the cerebrospinal fluid, urine and mucosa olfactoria. Areas covered: This analysis covers attempts of therapy in CJD and related diseases. It looks at problems encountered in designing and interpreting the few available trials with the aim that learning from past experiences would improve future clinical experimentations. Expert opinion: The future of therapeutic intervention in CJD should begin with the identification of novel compounds with strong antiprion effects. These need validating in animal models of disease before their use in humans. Improvement of preclinical studies according to internationally recognized guidelines should cover critical aspects that have been poorly followed in the past. The use of more than one model of prion infection should also be encouraged. Novel international diagnostic criteria for including CJD patients in clinical trials in an early stage are needed and consensus should be reached for determining the most meaningful criteria to evaluate the progression of disease.